A Holistic Proposal for English Elementary School Teachers’ Professional Development - Cadavid Múnera, Isabel Cristina; Quinchía Ortiz, Diana Isabel; Díaz, Claudia Patricia (Íkala, Revista de Lenguaje y Cultura, 2009)
This article presents the findings of an action research project carried out by a group of teachers and students from the Universidad de Antioquia. The action research project aimed to determine the impact of a professional development proposal for elementary school English teachers. In the first section, the article describes the project, including its objectives, the methodology used, and the theoretical framework that supports the proposal. In the second part, the findings obtained in the study are discussed in light of the objectives stated. Findings reveal that participant teachers improved both their use of the foreign language and their pedagogical practices as a result of having the opportunity to take risks and reflect as learners and teachers about holistic strategies for teaching and learning English as a foreign language. This work contributes to the construction of local knowledge in which university teachers as well as elementary school teachers work together to promote the construction of an academic community that encourages educational changes through professional development processes such as the one described in this article. Received: 29-08-08/ Accepted: 11-12-08 How to reference this article: Cadavid Munera, I. C.; Quinchia Ortiz, D. I. & Diaz Mosquera, C. P. (2009). Una propuesta holística de desarrollo profesional para maestros de inglés de la básica primaria. Íkala. 14(1), pp.135-158.